Product retrieval based on semantic similarity of consumer reviews to natural language query. (19th July 2010) - Sugiki, Kenji; Matsubara, Shigeki
In this paper, we propose a product retrieval method using product reviews. The method calculates the score of a product based on the similarity between a user's request extracted from a natural language query and consumers' opinions extracted from reviews of the product. We also propose the method to generate the thesaurus automatically from consumers' reviews. The thesaurus expresses semantic similarities between opinion expressions. We implemented an accommodation retrieval system and constructed the opinion thesaurus automatically from 652, 875 reviews. The experimental results show the effectiveness of our method.